Kepemimpinan Kolaboratif dan Partisipatif Kepala Sekolah dalam Meningkatkan Kinerja Guru di SDN Gambut 4 - Riski Adi Saputra; Nazarni Dara Puteri; Aslamiah Aslamiah; Celia Cinantya (CV. Global Cendekia Inti, 2026)
This study aims to analyze the implementation of collaborative and participatory leadership of the principal and its impact on teacher performance at SDN Gambut 4. The study employed a qualitative descriptive approach using a case study design. The research subjects consisted of the principal and teachers selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation, while data analysis was conducted using an interactive model, including data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation and member checking. The results show that collaborative leadership is implemented through teacher collaboration in planning, implementing, and evaluating learning, supported by open and dialogic communication. Participatory leadership is reflected in teachers’ active involvement in decision-making, program planning, and evaluation through deliberative forums. Task delegation and teacher empowerment further indicate the distribution of leadership roles (shared leadership), strengthening collective responsibility. These leadership practices positively impact teacher performance, as seen in improved lesson planning, increased discipline and responsibility, enhanced instructional innovation, and stronger collaboration among teachers. The findings also highlight the role of effective communication and a supportive school culture in sustaining these improvements. This study confirms that modern educational leadership should emphasize empowerment, collaboration, and active participation to enhance teacher performance and improve the quality of primary education.